The moorchild - McGraw, Eloise Jarvis (New York : Margaret K. McElderry Books/Aladdin Paperbacks, 1998)
Feeling that she is neither fully human nor "Folk," a changeling learns her true identity and attempts to find the human child whose place she had been given.
"A Margaret K. McElderry book.".
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Booklist starred, March 1996.
Elem. School Library Collection, June 2000.
Keywords: Fairies -- Fiction; Fantasy; Identity -- Fiction; Fairies -- Fiction; Individuality -- Fiction; Fantastic fiction